Mid and long-term ecological impacts of ski run construction on alpine ecosystems - Hudek, Csilla; Barni, Elena; Stanchi, Silvia; D’Amico, Michele; Pintaldi, Emanuele; Freppaz, Michele (Nature Publishing Group, 2020)
The proliferation of ski run construction is a worldwide trend. The machine-grading of slopes involved during ski run construction changes the physical, chemical and biological properties of the soil, having significant long-term ecological impact on the environment. Establishing and developing plant communities in these affected areas is crucial in rehabilitating the biotic and abiotic soil environment, while also improving slope stability and reducing the risk of natural hazards. This study evaluates changes in plant-soil properties and the long-term effects of machine-grading and subsequent restoration of ski runs so as to contribute to formulating the best practices in future ski run constructions. Study plots were established in 2000 and re-surveyed in 2017 on ski runs, which had been machine-graded and hydroseeded in the 1990s. Vegetation, root trait and soil surveys were carried out on ski run plots and compared to paired, undisturbed control sites off the ski runs. Plant cover remained unchanged on the ski-runs over time but plant richness and diversity considerably increased, reaching similar levels to undisturbed vegetation. Plant composition moved towards more semi-natural stages, showing a reduction in seeded plants with a comparable increase in the cover of colonizing native species. Root trait results were site-specific showing great variations between the mid and long-term after-effects of machine-grading and revegetation when compared to undisturbed sites. Under long-term management, the soil pH was still higher and the organic C content still lower in the ski runs than in the undisturbed sites, as the aggregate stability. The standard actions applied (machine-grading, storage and re-use of topsoil, hydroseeding of commercial seed mixtures, application of manure soon after seeding and low-intensity grazing) allowed the ecosystem to partially recover in three decades, and even if the soil has still a lower chemical and physical fertility than the undisturbed sites, the plant species composition reveals a satisfactory degree of renaturalization.